Antioxidant properties of Komagataeibacter hansenii CGMCC 3917 and its ameliorative effects on alcohol-induced liver injury in mice. Issue 1 (1st January 2019) - Jiang, Xinxin; Lin, Dehui; Shao, Hongjun; Yang, Xingbin
ABSTRACT: This study was to investigate the antioxidant activity of Komagataeibacter hansenii CGMCC 3917 in vivo and in vitro. In vitro study suggested that CGMCC 3917 exhibited strong scavenging abilities against DPPH, ABTS, OH free radicals and reducing power, suggesting significant anti-oxidant ability. In vivo supplementation of mice with CGMCC 3917 bacteria suspension at a dose of 10 mL/kg (10 8 or 10 6 CFUs/mL) dramatically decreased the elevated serum activities of aspartate aminotransferase (AST) and alanine aminotransferase (ALT) induced by alcohol treatment in mice ( p < 0.01), and also significantly decreased the elevated levels of alkaline phosphatase (ALP) and hepatic malondialdehyde (MDA) induced by alcohol treatment in mice ( p < 0.01). Furthermore, CGMCC 3917 supplement showed the preventive effects against the alcohol-induced elevation in serum triglycerides (TG) and low-density lipoprotein cholesterol (LDL-C), and the decrease in high-density lipoprotein cholesterol (HDL-C), as well as the decreased activities of glutathione peroxidase (GSH-P x ) and superoxide dismutase (SOD) in mice. Additionally, supplementation with CGMCC 3917 displayed significant anti-inflammatory effects by lowering hepatic production of TNF-α, IL-1, and IL-6 in alcohol-treated mice. All these findings suggest that K. hansenii CGMCC 3917 may be a great potential nutritional resource against chronic alcohol-induced liver oxidative injury in mice.